2006
DOI: 10.1007/s00220-006-0080-7
|View full text |Cite
|
Sign up to set email alerts
|

Birkhoff Type Decompositions and the Baker–Campbell–Hausdorff Recursion

Abstract: Abstract. We describe a unification of several apparently unrelated factorizations arisen from quantum field theory, vertex operator algebras, combinatorics and numerical methods in differential equations. The unification is given by a Birkhoff type decomposition that was obtained from the Baker-Campbell-Hausdorff formula in our study of the Hopf algebra approach of Connes and Kreimer to renormalization in perturbative quantum field theory. There we showed that the Birkhoff decomposition of Connes and Kreimer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 68 publications
(117 citation statements)
references
References 33 publications
0
116
0
1
Order By: Relevance
“…Given the recent progresses on Rota-Baxter algebra in both theoretical and applied aspects [1,2,10,[15][16][17][18][19][24][25][26][27][28][29][30][31], it is desirable to obtain convenient constructions of free Rota-Baxter algebras. To this end, in Section 5, we put together bijections and inclusions among bracketed words, Motzkin path, vertex decorated forests and angularly decorated forests, as well as their various subsets (Theorem 5.1).…”
Section: Outline Of the Papermentioning
confidence: 99%
“…Given the recent progresses on Rota-Baxter algebra in both theoretical and applied aspects [1,2,10,[15][16][17][18][19][24][25][26][27][28][29][30][31], it is desirable to obtain convenient constructions of free Rota-Baxter algebras. To this end, in Section 5, we put together bijections and inclusions among bracketed words, Motzkin path, vertex decorated forests and angularly decorated forests, as well as their various subsets (Theorem 5.1).…”
Section: Outline Of the Papermentioning
confidence: 99%
“…For more details we refer the reader to the classical papers [2], [3], [6], [45], [46], as well as for instance to the references [22], [19].…”
Section: Rota-baxter Algebras and Bogoliubov's Recursionmentioning
confidence: 99%
“…However, as we mentioned, in renormalization the very RB structure one has to deal with is noncommutative, so that these results do not apply. In [17] it was shown that one can prove a first noncommutative Spitzer (also known as Pollaczeck-Spitzer) identity, and that this identity was related to a so-called BakerCampbell-Hausdorff (BCH) recursion, which is another way, besides Bogoliubov's, to perform recursively the renormalization process [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…The other operators are also important. For example, the Rota-Baxter operator, which originated from probability study [9], is closely related to the classical Yang-Baxter equation, as well as to operads, to combinatorics and, through the Hopf algebra framework of Connes and Kreimer, to the renormalization of quantum field theory [2,3,8,5,17,19,20,18,24,25,28].…”
Section: P(x)p(y) = P(xp(y) + P(x)y − P(x)p(y))mentioning
confidence: 99%